The 2030 Declaration on Scientific Plant and Fungal Collecting - Alexandre Antonelli; Jordan K. Teisher; Rhian J. Smith; A. Martyn Ainsworth; Giuliana Furci; Ester Gaya; Susana C. Gonçalves; David L. Hawksworth; Isabel Larridon; Emily B. Sessa; Ana Rita G. Simões; Laura M. Suz; et al. (Plants, People, Planet)
Societal Impact Statement Biological samples and their associated information are an essential resource used by scientists, governments, policymakers, practitioners and communities to ensure that biodiversity can be appropriately protected and sustainably used. Yet, considering the enormous task of documenting the vast numbers of as‐yet‐unknown plant and fungal species, greater international coordination for biological collecting and recording is necessary, built on equitable collecting practices and standards. Here, we propose five commitments to accelerate and enhance scientific knowledge of plant and fungal diversity, while increasing collaboration, benefit sharing and efficiency. Summary Almost all life depends on plants and fungi, making knowledge of their diversity and distribution—primarily derived from biological collections—fundamental to national and international conservation, restoration and sustainable use commitments. However, it is estimated that some 15% of all plant species and over 90% of all fungal species have not yet been scientifically described, hampering our ability to assess and demonstrate the impact of efforts to halt biodiversity loss. In addition, organisations and researchers around the world lack a concerted strategy for increasing complementarity and avoiding overlap in botanical and mycological research, particularly in relation to the collection of specimens. We here present the 2030 Declaration on Scientific Plant and Fungal Collecting, summarising a commitment towards such a necessary strategy. Its components were identified from discussions during and after a series of four workshops and plenary discussions at the 2023 State of the World's Plants and Fungi symposium convened by the Royal Botanic Gardens, Kew, and were then consolidated into the present form by the authors. The Declaration was subsequently opened up for endorsement by signatories. Collectively, we agree on a set of five commitments for cataloguing the world's flora and funga, designed to maximise efficiency, facilitate knowledge exchange and promote equitable collaborations: (1) use evidence‐based collection strategies; (2) strengthen local capacity; (3) collaborate across taxa and disciplines; (4) collect for the future; and (5) share the benefits. This Declaration is a first step towards increased global and regional coordination of scientific collecting efforts.